Evaluation of Turkic Republics In Terms of Business Feasibility Potential - Dilek, Serkan; Konak, Ali (Eurasian Economists Association, 2015)
Today, level of countries’ business feasibility in terms of global competition has a great importance. For businessmen, determination of the level of countries’ business feasibility provides important information about the level of overall business feasibility of the examined countries and plays an important role on understanding the levels of the investment feasibility of countries. In this context, in our search, the levels of business feasibility of countries Azerbaijan, Kazakhstan, and Kyrgzstan presenting available business feasibility index and Global Competitiveness Index between 2004-2014 has been examinated with the help of the business feasibility index prepared by World Economic Forum (WEF), thus it has been trying to put forward strengths and weaknesses in terms of getting feasibility business in these countries. As a result of studies, with together change from country to country and from year to year, the most important barriers in front of the feasibility business in the examined Turkic Republics in recent years, has been determined that they are based on inability to access enough to an electrical source, the lack of protection of investors and inability to perform remarkable progress in the matter of tax paid. After all, in Turkish Republics, it was that there are positive developments in the process of starting work, also significantly reduced in bankruptcy, besides, the realization of significant progress about formalization of property and reaching credit resources and in line with these developments, it has been concluded that Turkic Republics -except Tajikistan- has slightly developments in being business feasible country.
Keywords: 9. Industry and infrastructure; 11. Sustainability; 8. Economic growth; 1. No poverty; 12. Responsible consumption